2019
DOI: 10.1021/acs.joc.9b00990
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of N-Imidoyl-(1H)-indoles via Palladium-Catalyzed Oxidative Insertion Domino Reaction with Isocyanide and Arylboronic Acid

Abstract: Efficient one-pot synthesis of N-imidoyl-(1H)indoles has been described, which is achieved by the palladium-catalyzed oxidative insertion of 2-(phenylethynyl)aniline, arylboronic acid, and isonitrile. This method provides a new way to synthesize N-imidoyl-(1H)-indoles, which has a wide substrate scope, good functional group tolerance, and mild reaction condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In 2019 Ya-Ping Han et al [37] reported Lewis acid (Cu(OTf) 2 ) catalyzed synthesis of 1-H-Pyrrolo[1,2-a] indoles 61 (Scheme 20) from commercially available propargylic alcohols 59 and 2ethynylanilines 60 by annulation approach. [38] The survey of various reaction conditions disclosed that better yields of 1-H-Pyrrolo[1,2-a] indoles 61 were obtained under 15 mol% of copper triflate in dichloroethane solvent for reflux at 6 h. In addition, it was found that temperature of the reaction has significant impact on the yield of the reaction. upon increasing the reaction temperature found tremendous increase in the yields of the desired product.…”
Section: Scheme 10 Cascade Reactions Of Anilines With Diynesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019 Ya-Ping Han et al [37] reported Lewis acid (Cu(OTf) 2 ) catalyzed synthesis of 1-H-Pyrrolo[1,2-a] indoles 61 (Scheme 20) from commercially available propargylic alcohols 59 and 2ethynylanilines 60 by annulation approach. [38] The survey of various reaction conditions disclosed that better yields of 1-H-Pyrrolo[1,2-a] indoles 61 were obtained under 15 mol% of copper triflate in dichloroethane solvent for reflux at 6 h. In addition, it was found that temperature of the reaction has significant impact on the yield of the reaction. upon increasing the reaction temperature found tremendous increase in the yields of the desired product.…”
Section: Scheme 10 Cascade Reactions Of Anilines With Diynesmentioning
confidence: 99%
“…Yong-Ming Zhu et al [38] described a novel Pd(II) catalyzed one pot synthesis of N-imidoyl-(1H)-indoles 86 (scheme 28) from 2-(phenylethynyl)-anilines 83 arylboronic acids 84, and isonitriles 85. [59] Herein, 2-(phenylethynyl)-anilines 83 arylboronic acids 84, and isonitriles 85 undergo palladium catalysed oxidative insertion with Cu (OAc) 2 as oxidant, DMF as solvent at 100°C to give desired indole derivative.…”
Section: Palladium-catalysed Synthesis Of Indolesmentioning
confidence: 99%
“…Although the isocyanide is cleaved off, the authors showed that this homocoupling is compatible with several isocyanides, mirroring the efficiency shown for the synthesis of benzamides 283. Pd-catalyzed imidoylative Buchwald-Hartwig reaction can also be combined with a cascade transition metal-catalyzed cyclization [127]. Transmetalation with arylboronic acids and 1,1migratory insertion of the isocyanide affords the imidoyl palladium species 290, which is subsequently trapped by the nucleophilic 2-alkynylaniline 296 (Scheme 77).…”
Section: Scheme 69mentioning
confidence: 99%
“…Our group reported one of the first aerobic Pd-catalyzed formation of benzoxazinones 293 through the direct coupling of anthranilic acids 292 with isocyanides (Scheme 78) [128]. The reaction Pd-catalyzed imidoylative Buchwald-Hartwig reaction can also be combined with a cascade transition metal-catalyzed cyclization [127]. Transmetalation with arylboronic acids and 1,1-migratory insertion of the isocyanide affords the imidoyl palladium species 290, which is subsequently trapped by the nucleophilic 2-alkynylaniline 296 (Scheme 77).…”
Section: Pd II -Catalyzed Intramolecular Oxidative Isocyanide Insertionsmentioning
confidence: 99%
See 1 more Smart Citation